Performance Evaluation of an Automatic Mixing Bed Dryer for Paddy Using Corncob Biomass Fuel - Siswoyo Soekarno; Apriza Fatkur Roziqin; Ning Puji Lestari; Rufiani Nadzirah (The University of Lampung, 2026)
Drying is an essential stage in post-harvest rice handling to reduce the moisture content to a safe storage level (≤14%). This study aimed to evaluate the field performance of a bed dryer automixing type rice dryer fueled by corncob biomass. The experiment was conducted at the Organic Rice Mill Tani Jaya II, Rowosari Village, Jember Regency, with three actual drying capacities of 1 ton, 1.2 ton, and 1.7 ton of paddy. The observed parameters included temperature distribution, moisture reduction, drying rate, and energy efficiency. The results showed that the highest temperature occurred in the lower layer of the paddy bed (35.5 ‐ 41 °C), while the final moisture content in all treatments was below 14%. The drying rate fluctuated due to the mixing process and variations in hot air temperature, with the highest efficiency obtained at a capacity of 1.7 ton (58.32%). These findings indicate that the bed dryer automixing type rice dryer performs effectively under field conditions with varying load capacities and is suitable to be applied as a biomass based drying solution that can accelerate the drying process and operate effectively during the rainy season.